Pola Makan Dan Status Gizi Anak Usia Sekolah Dasar di Wilayah Pedesaan Dan Perkotaan - Salsabila, Diya; Hidayanti, Lilik; Listyawardhani, Yana (JURNAL RISET GIZI, 2023)
ABSTRACTBackground: Access to food differs between school-age children in rural and urban areas which is thought to have an impact on differences in the eating patterns and nutritional status of school-age children. The purpose of this study was to analyse differences in food pattern and nutritional status of school-age children in rural and urban areas.Methods: This research is a cross-sectional design. SDN I Benda which is located in Tasikmalaya City represents an urban area and SDN 3 Sukasari in Ciamis represents a rural area. The number of subjects in rural areas is 38 students and in urban areas is 40 students. Differences in eating patterns in rural and urban areas were analysed using independent t-test and Mann-Whitney at significance (p<0.05).Results: The average food diversity of school-age children in rural areas (4) is less than in urban areas (4.5). The intake of energy (1636.8 vs 1526.1 kcal), protein (47.2 vs 43 g), fat (71 vs 62.8 g) and carbohydrates (214.1 vs 120.8 g) of school-age children in rural areas is slightly higher than in urban areas. This study showed that there were differences in the food diversity of school-age children in rural and urban areas (p=0.003); but there was no difference in energy (p=0.280), protein (p=0.593), fat (p=0.154), and carbohydrate (p=0.308) intake of school-age children in rural and urban areas.Conclusion: The food diversity of school-age children in rural areas is less than in urban areas, therefore efforts are needed to increase food diversity in rural areas